Depression promotes prostate cancer invasion and metastasis via a sympathetic-cAMP-FAK signaling pathway - Cheng, Yan (2018)
Fil: Cheng, Yan. China Pharmaceutical University. Center for New Drug Safety Evaluation and Research. State Key Laboratory of Natural Medicines. Key Laboratory of Drug Discovery for Metabolic Disease; China